The New England gazetteer containing descriptions of all the states, counties and towns in New England: also, descriptions of the principal mountains, rivers, lakes, capes, bays, harbors, islands, and fashionable resorts within that territory. - Hayward, John, 1781-1869. (Tufts University. Tisch Library., 2015)
9th ed.; 1 online resource ([510] pages)frontispiece, illustrations, plates.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.